2017
DOI: 10.1016/j.wem.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Field Wound Care: Prophylactic Antibiotics

Abstract: Adequate management of wounds requires numerous interventions, one of which is the appropriate use of antimicrobials to attempt to minimize the risk of excess morbidity or mortality without increasing toxicity or multidrug resistant bacterial acquisition. There are numerous recommendations and opinions for not only the use of systemic prophylactic antimicrobials, but also the agent, dose, route, and duration. To best address the implementation of systemic antimicrobials in a field scenario, one must weigh the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 87 publications
0
10
0
1
Order By: Relevance
“…Many other systemic drugs (e.g., aspirin, flavonoids, thromboxane alpha-2 agonists, sulodexide) improve the wound environment [94][95][96][97]. However, caution in the use of this latter treatment is needed to evaluate if the benefits overcome their associated risks: antimicrobial resistance, allergic reactions, drug toxicities (cardiac, hepatic, renal, and hematopoietic), and drug interactions [98].…”
Section: Non-phage-based Wound Treatmentsmentioning
confidence: 99%
“…Many other systemic drugs (e.g., aspirin, flavonoids, thromboxane alpha-2 agonists, sulodexide) improve the wound environment [94][95][96][97]. However, caution in the use of this latter treatment is needed to evaluate if the benefits overcome their associated risks: antimicrobial resistance, allergic reactions, drug toxicities (cardiac, hepatic, renal, and hematopoietic), and drug interactions [98].…”
Section: Non-phage-based Wound Treatmentsmentioning
confidence: 99%
“…There is difficulty identifying the best antimicrobial for POI use. Despite Gram-negative bacteria being predominate in infected combat wounds, studies have also shown Gram-positive infective wounds including methicillin-resistant Staphylococcus aureus 3 27 32 33. Therefore, a POI antibiotic cannot have purely Gram-negative activity.…”
Section: Againstmentioning
confidence: 99%
“…Therefore, a POI antibiotic cannot have purely Gram-negative activity. Recent research has shown that the US military POI antibiotic, moxifloxacin, has poor P. aeruginosa cover and has actually resulted in increased drug resistance of Bacteroides sp 33–35. There is even some evidence to suggest that wound infections usually occur in patients while in hospital and not at POI.…”
Section: Againstmentioning
confidence: 99%
See 2 more Smart Citations